PROFIL MAHASISWA PENERIMA KIP TAHUN 2021 PROGRAM STUDI PPKNUNIVERSITAS BHINNEKA PGRI TULUNGAGUNG - Bagas Rizky Hermawan; Nurna Listya Purnamasari; Andreas Andrie Djatmiko (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to analyze the profile of students receiving the Smart Indonesia Card (KIP) in the Civic Education (PPKn) Study Program at Bhinneka PGRI University Tulungagung. The focus of the research includes the students' socio-economic backgrounds, academic achievements, and strategies to maintain their Grade Point Average (GPA). KIP is a government scholarship program designed to support academically talented students from underprivileged families to access quality higher education. This research employed a qualitative descriptive approach using data collection techniques including observation, in-depth interviews, and documentation. The findings revealed that most KIP recipients came from lower-middle-class families, made considerable efforts to sustain academic performance, and implemented strategies such as time management, intrinsic motivation, and social support. Moreover, they faced challenges such as academic pressure and a lack of engagement in non-academic activities. The study concludes that student success under the KIP program is not solely determined by financial support but also by psychological readiness, a conducive learning environment, and personal strategies applied consistently.